Preparation method of epoxy resin-based high-electrical-strength composite insulating material

By introducing fluorine-containing epoxy monomers and curing agents to form a high crosslink density network and using modified nanofillers, the problem of deterioration of insulation performance of epoxy resin-based insulating materials is solved, and the electrical strength and aging resistance of the material are improved, especially the stability in high temperature, high humidity and ultraviolet environments.

CN120271961APending Publication Date: 2025-07-08NANNING NANTE TRANSFORMER MFG

Patent Information

Application Number
CN202510361486.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

Traditional epoxy resin-based insulating materials are susceptible to thermal oxygen, corona discharge and chemical media during long-term service, resulting in deterioration of insulation performance and attenuation of mechanical properties. Fluorine-containing modification is difficult to improve the compatibility and interface defects of the material, limiting the improvement of the comprehensive performance of composite materials.

Method used

The compatibility and dispersion of the material are enhanced by introducing fluorine-containing epoxy monomers and fluorine-containing curing agents.

Benefits of technology

It significantly improves the electrical strength and aging resistance of composite insulating materials, and extends the service life of the material in complex environments, especially the stability of the heat, humidity and ultraviolet conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method of an epoxy resin-based high-electrical-strength composite insulating material. The preparation method comprises the following steps: carrying out ring opening polymerization on 100 parts by weight of epoxy resin matrix and 0.5-10 parts by weight of fluorine-containing epoxy monomer under the action of 0.1-1 part by weight of catalyst to generate fluorine-containing modified epoxy resin; then carrying out a curing reaction with 30-50 parts by weight of a fluorine-containing aromatic amine curing agent to form a high-crosslinking-density network structure; then blending with 2-4 parts by weight of nano filler; and finally, carrying out vacuum degassing, injecting into a mold, and carrying out pre-curing and post-curing to obtain the material. According to the method, the fluorine-containing monomer and the curing agent are introduced, and the nano filler is combined, so that the electrical strength, the aging resistance and the long-term stability of the composite insulating material are remarkably improved, and the composite insulating material has a wide application prospect in the fields of power transmission, electronic packaging, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of insulating materials. More specifically, the present invention relates to a preparation method of an epoxy resin-based composite insulating material with high electrical strength. Background Art

[0002] Epoxy resin-based insulating materials play an irreplaceable role in fields such as power transmission, electronic packaging, and aerospace. However, during their long-term service, they face challenges from multiple aging mechanisms. In the molecular chains of traditional bisphenol A epoxy resins, polar groups such as ether bonds and hydroxyl groups are prone to thermal oxidation, corona discharge, and chemical medium erosion, leading to deterioration of insulation performance and attenuation of mechanical properties. For example, in ultra-high voltage power transmission and transformation equipment, corona discharge on the material surface can trigger a chain oxidation reaction, causing carbonization failure of the insulation layer; in a humid and hot environment, the hydrolysis reaction of epoxy materials can lead to the breakage of the cross-linked network and a significant shortening of the service life.

[0003] Existing modification strategies mainly improve the anti-aging performance by introducing functional monomers or nano-fillers. Fluorine-containing compounds have been widely studied due to their unique molecular structures (such as low surface energy and high bond energy C-F bonds): perfluoroalkyl chains can endow materials with excellent hydrophobicity and chemical corrosion resistance, and fluorine-containing aromatic rings can enhance the rigidity of molecular chains through conjugation effects. However, traditional fluorine-containing monomers (such as hexafluorobisphenol A) have poor compatibility with epoxy resins, and the fluorinated structure is prone to phase separation during the curing process, resulting in a decrease in the mechanical properties of the material. In addition, simple fluorination modification is difficult to inhibit the interfacial defects between nano-fillers and the resin matrix, limiting the improvement of the comprehensive performance of the composite material. Summary of the Invention

[0004] An object of the present invention is to solve at least the above problems and provide at least the advantages described hereinafter.

[0005] Another object of the present invention is to provide a preparation method of an epoxy resin-based composite insulating material with high electrical strength, which forms a fluorinated epoxy resin network structure with a high cross-linking density by introducing fluorine-containing epoxy monomers and fluorine-containing curing agents, and adding nano-fillers, significantly improving the electrical strength, anti-aging performance, and long-term stability of the composite insulating material.

[0006] To achieve these objects and other advantages according to the present invention, there is provided a preparation method of an epoxy resin-based composite insulating material with high electrical strength, which includes the following steps: Step 1: Subject 100 parts by weight of an epoxy resin matrix and 0.5 - 10 parts by weight of a fluorine-containing epoxy monomer to ring-opening polymerization reaction under the action of 0.1 - 1 part by weight of a catalyst to generate fluorine-containing modified epoxy resin; wherein, the fluorine-containing epoxy monomer is selected from perfluoroalkyl epoxy monomers or fluorine-containing aromatic ring epoxy monomers, and the catalyst is a Lewis acid or a basic catalyst; Step 2: Mix the fluorinated modified epoxy resin with 30 - 50 parts by weight of a fluorinated curing agent, which is selected from fluorinated aromatic amine curing agents, and carry out a curing reaction to form a fluorinated epoxy resin network structure with a high crosslinking density; the fluorinated curing agent is 4,4'-diaminooctafluorobiphenyl; Step 3: Blend 1.9 - 5.6 parts by weight of nano-fillers with the fluorinated epoxy resin network structure; Step 4: After subjecting the mixed liquid to vacuum degassing, inject it into a mold, pre-cure it at 80 - 90 °C for 3 - 5 h, and then post-cure it at 110 - 130 °C for 7 - 9 h to obtain an epoxy resin-based composite insulating material with high electrical strength. By introducing epoxy resin modified with fluorine-containing anti-aging functional groups, the present invention solves the problem of long-term stability of epoxy resin-based composite insulating materials.

[0007] Preferably, the nano-fillers are surface-modified nano-silica, and the modification method includes the following steps: a) Disperse 1 part by weight of nano-silica in 50 parts by weight of absolute ethanol and perform ultrasonic treatment for 30 min; b) Add 0.2 part by weight of perfluorooctyltriethoxysilane (PFOTES), and stir and react at 60 °C to cause the hydrolysis and condensation reaction between perfluorooctyltriethoxysilane and the hydroxyl groups on the surface of nano-silica; c) After the reaction ends, centrifuge and separate the mixture, wash it 3 times with absolute ethanol to remove the unreacted perfluorooctyltriethoxysilane, and dry it to obtain surface-modified nano-silica (PFOTES-SiO2). By modifying the surface of the nano-fillers, the present invention solves the problem of poor compatibility between the fluorinated modified epoxy resin and the nano-fillers after introducing fluorine-modified epoxy resin.

[0008] Preferably, 0.1 - 0.5 part by weight of nano-clay is further added in step a) during the preparation of the surface-modified nano-silica; 0.01 - 0.05 part by weight of an acidic catalyst is further added in step b). By introducing nano-clay, the present invention solves the problem that the perfluoroalkylsilane modification layer is prone to degradation or peeling during long-term use, especially in high-temperature, high-humidity or strong ultraviolet environments.

[0009] Preferably, the ultrasonic power is 200 w.

[0010] Preferably, the drying temperature is 60 - 80 °C.

[0011] Preferably, in step B), the stirring speed is 300 - 500 rpm and the time is 6 h.

[0012] Preferably, in step C), the centrifugation speed is 3000 - 5000 rpm and the time is 10 - 20 min.

[0013] Preferably, the acidic catalyst is one of acetic acid or citric acid.

[0014] Preferably, the nanoclay is also subjected to a composite treatment with graphene quantum dots, which specifically includes the following steps: 1) Add 5 parts by weight of nanoclay into a container containing 100 parts by volume of DMF, and disperse it under ultrasonic environment for 30 - 60 min to preliminarily disperse the nanoclay evenly; then, slowly add 50 parts by volume of graphene quantum dot solution with a concentration of 1 mg / mL, and continue ultrasonic dispersion for 2 - 4 h to enable full contact and interaction between the graphene quantum dots and the nanoclay; 2) Centrifuge the ultrasonically dispersed mixed solution to remove impurities and unreacted substances in the supernatant, and then wash the precipitate with DMF multiple times to ensure that the surface impurities are completely removed; 3) Dry the washed precipitate in a vacuum oven to obtain the nanoclay - graphene quantum dot composite powder, which can be used for composite modification of nano - silica with perfluoroalkylsilane.

[0015] By compounding the nanoclay with graphene quantum dots, the present invention further solves the problem of the dispersibility of nanoclay in the application of composite materials.

[0016] Preferably, in step 2), the rotation speed is controlled at 5000 - 8000 rpm and the time is 15 - 30 min; in step 3), the temperature is set at 60 - 80 °C and the drying time is 12 - 24 h.

[0017] The present invention has at least the following beneficial effects: First, by introducing fluorinated epoxy monomers and fluorinated curing agents, a fluorinated epoxy resin network structure with high cross - link density is formed, and nano - fillers are added, significantly improving the electrical strength of the composite insulation material and better meeting the high requirements for insulation performance in fields such as power transmission. Second, after surface modification of the nano - silica of the present invention, compounding with nanoclay, and the composite treatment of nanoclay with graphene quantum dots, the particle size distribution continuously decreases and the dispersibility gradually increases, making the internal structure of the material more uniform and helping to improve the comprehensive performance of the material. Third, the material of the present invention has excellent aging resistance under thermal and humid - heat environments, and can effectively extend the service life in complex environments.

[0018] Other advantages, objectives, and features of the present invention will be partially reflected by the following description and partially understood by those skilled in the art through the research and practice of the present invention. Detailed implementation mode

[0019] The following further detailed description of the present invention is provided to enable those skilled in the art to implement it with reference to the text of the specification.

[0020] It should be understood that terms such as "having", "comprising", and "including" as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0021] It should be noted that the experimental methods described in the following embodiments are all conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial sources unless otherwise specified.

[0022] <Example 1> A preparation method of an epoxy resin-based composite insulating material with high electrical strength, which comprises the following steps: Step 1: Ring-opening polymerization reaction is carried out on 100 g of epoxy resin matrix and 5 g of fluorinated epoxy monomer under the action of 0.5 g of catalyst to generate fluorinated modified epoxy resin; wherein, the fluorinated epoxy monomer is selected from perfluoroalkyl epoxy monomer or fluorinated aromatic ring epoxy monomer, and the catalyst is Lewis acid or basic catalyst; Step 2: Mix the fluorinated modified epoxy resin with 40 g of fluorinated curing agent, and the fluorinated curing agent is selected from fluorinated aromatic amine curing agent, and carry out curing reaction to form a fluorinated epoxy resin network structure with high cross-linking density; the fluorinated curing agent is 4,4'-diaminooctafluorobiphenyl; Step 3: Blend 3 g of nano-fillers with the fluorinated epoxy resin network structure; the nano-fillers are nano-silica; Step 4: After vacuum degassing the mixed solution, inject it into a mold, pre-cure at 80 °C for 4 h, and then post-cure at 120 °C for 8 h to obtain an epoxy resin-based composite insulating material with high electrical strength.

[0023] <Example 2> A preparation method of an epoxy resin-based composite insulating material with high electrical strength, which is different from <Example 1> in that the nano-fillers are surface-modified nano-silica, and its modification method comprises the following steps: a) Disperse 1 g of nano-silica in 50 g of absolute ethanol, with an ultrasonic power of 200 w and a treatment time of 30 min; b) Add 0.2 g of perfluorooctyltriethoxysilane (PFOTES), stir and react at 60 °C, with a stirring speed of 100 rpm and a time of 6 h, so that perfluorooctyltriethoxysilane undergoes hydrolysis and condensation reaction with the hydroxyl groups on the surface of nano-silica; c) After the reaction is completed, centrifuge the mixture at a speed of 4000 rpm for 10 min, wash it 3 times with absolute ethanol to remove the unreacted perfluorooctyltriethoxysilane, and dry it at 60 °C to obtain surface-modified nano-silica (PFOTES-SiO2).

[0024] Example 3 A preparation method of an epoxy resin-based composite insulating material with high electrical strength, which is different from <Example 2> in that During the preparation of surface-modified nano-silica, 0.4 g of nano-clay is further added in step a); 0.04 g of acidic catalyst is added in step b).

[0025] Example 4 A preparation method of an epoxy resin-based composite insulating material with high electrical strength, which is different from <Example 3> in that the nano-clay is also subjected to a composite treatment with graphene quantum dots, and specifically includes the following steps: 1) Add 5 g of nano-clay to a container containing 100 mL of DMF, disperse it under ultrasonic environment for 40 min to make the nano-clay preliminarily dispersed evenly; then, slowly add 50 mL of graphene quantum dot solution with a concentration of 1 mg / mL, and continue ultrasonic dispersion for 2 - 4 h to make the graphene quantum dots fully contact and interact with the nano-clay; 2) Centrifuge the ultrasonically dispersed mixed solution, control the rotation speed at 6000 rpm for 20 min, remove the impurities and unreacted substances in the supernatant, and then wash the precipitate with DMF multiple times to ensure that the surface impurities are completely removed; 3) Dry the washed precipitate in a vacuum oven at a temperature of 60 °C for 20 h to obtain nano-clay-graphene quantum dot composite powder, which can be used for composite modification of nano-silica with perfluoroalkylsilane.

[0026] Effect test Comparative Example 1: Epoxy resin-based insulating material purchased from the market.

[0027] I. Electrical strength test Test standard: IEC 60243-1 Sample preparation: Samples of Examples 1 - 4 and Comparative Example 1 are all made into 1-mm-thick thin slices with a flat and defect-free surface.

[0028] Test conditions: Voltage rising rate: 1 kV / s Environment: 25 ± 2 °C, 50 ± 5% RH Test steps: Place the sample between the electrodes and gradually apply an alternating voltage until breakdown.

[0029] Record the breakdown voltage value and calculate the electrical strength (kV / mm). The results are shown in Table 1.

[0030] Table 1 Electrical strength test results As can be seen from the results in Table 1, the introduction of fluorine modification and nano-fillers significantly improves the electrical strength of the composite insulation material, and the optimization of the composite filler further enhances this effect.

[0031] II. Aging Experiments 1. Thermal Aging Test Test conditions: 150 °C, 1000 hours.

[0032] Evaluation index: Electrical strength retention rate (after aging / before aging × 100%).

[0033] The results of the thermal aging test are shown in Table 2.

[0034] Table 2 Electrical strength retention rate of the thermal aging test As can be seen from the results in Table 2, the introduction of fluorine modification and nano-fillers significantly improves the thermal stability of the composite insulation material, and the optimization of the composite filler further enhances this effect.

[0035] 2. Damp Heat Aging Test Test conditions: Temperature 85 °C, relative humidity 85%, time 500 hours.

[0036] Evaluation indexes: Water absorption rate (%) and electrical strength retention rate.

[0037] The results of the damp heat aging test are shown in Table 3.

[0038] Table 3 Electrical strength retention rate and water absorption rate of the damp heat aging test As can be seen from the results in Table 3, the introduction of fluorine modification and nano-fillers significantly improves the damp heat resistance of the composite insulation material, and the optimization of the composite filler further enhances this effect.

[0039] 3. UV Aging Test conditions: Irradiation intensity is set to 0.71 W / m² @ 340 nm, 200 hours.

[0040] Evaluation index: Surface color change (ΔE value).

[0041] The results of the UV aging are shown in Table 4.

[0042] Table 4 Surface color change of the UV aging test As can be seen from the results in Table 4, the introduction of fluorine modification and nano-fillers significantly improves the UV aging resistance of the composite insulation material, and the optimization of the composite filler further enhances this effect.

[0043] III. Characterization of filler dispersibility In the present invention, transmission images of ultra-thin samples are obtained by transmission electron microscopy (TEM), and the particle size distribution of nano-fillers is statistically analyzed by the image analysis software ImageJ. The results are shown in Table 5.

[0044] Table 5 Particle size distribution of nano-fillers From the results in Table 5, it can be seen that in Example 1, the unmodified nano-SiO2 has a relatively high surface energy and partial agglomeration occurs. In Example 2, the nano-silica is treated with a silane coupling agent, the surface energy of the particles is reduced, and the dispersibility is improved. In Example 3, nano-clay is added, the particle size distribution is reduced, and the dispersibility is enhanced. In Example 4, after the nano-clay is compounded with graphene quantum dots, the particle size distribution is further reduced, and the dispersibility is enhanced.

[0045] Although the embodiments of the present invention have been disclosed as above, it is not limited to the applications listed in the specification and embodiments. It can be fully applied to various fields suitable for the present invention. For those skilled in the art, additional modifications can be easily made. Therefore, without departing from the general concept defined by the claims and the equivalent scope, the present invention is not limited to specific details.

Claims

1. Preparation method of epoxy resin-based composite insulating material with high electrical strength, characterized in that, It includes the following steps: Step 1: Carry out a ring-opening polymerization reaction on an epoxy resin matrix and a fluorinated epoxy monomer under the action of a catalyst to generate a fluorinated modified epoxy resin; wherein, the fluorinated epoxy monomer is selected from perfluoroalkyl epoxy monomers or fluorinated aromatic ring epoxy monomers, and the catalyst is a Lewis acid or a basic catalyst; Step 2: Mix the fluorinated modified epoxy resin with a fluorinated curing agent, and the fluorinated curing agent is selected from fluorinated aromatic amine curing agents, and carry out a curing reaction to form a fluorinated epoxy resin network structure with a high cross-linking density; the fluorinated curing agent is 4,4'-diaminooctafluorobiphenyl; Step 3: Blend the nano-fillers with the fluorinated epoxy resin network structure; Step 4: Carry out vacuum degassing on the mixed solution and then inject it into a mold, pre-cure it at 80-90 °C for 3-5 h in sequence, and then post-cure it at 110-130 °C for 7-9 h to obtain an epoxy resin-based composite insulating material with high electrical strength.

2. The preparation method of the epoxy resin-based composite insulating material with high electrical strength according to claim 1, characterized in that, The nano-fillers are surface-modified nano-silica, and its modification method includes the following steps: a) Disperse 1 part by weight of nano-silica in 50 parts by weight of absolute ethanol and ultrasonically treat it for 30 min; b) Add 0.2 part by weight of perfluorooctyltriethoxysilane, stir and react at 60 °C to cause the hydrolysis and condensation reaction of perfluorooctyltriethoxysilane with the hydroxyl groups on the surface of nano-silica; c) After the reaction ends, centrifuge and separate the mixture, wash it 3 times with absolute ethanol to remove the unreacted perfluorooctyltriethoxysilane, and dry it to obtain surface-modified nano-silica.

3. The preparation method of the epoxy resin-based composite insulating material with high electrical strength according to claim 2, wherein, In step b), the stirring speed is 50-100 rpm and the time is 6 h.

4. The preparation method of the epoxy resin-based composite insulating material with high electrical strength according to claim 2, wherein, In step c), the rotation speed of the centrifuge separation of the mixture is 3000-5000 rpm and the time is 10-15 min.

5. The preparation method of the epoxy resin-based high electrical strength composite insulating material according to claim 2, characterized in that, During the process of preparing the surface-modified nano-silica, 0.1-0.5 part by weight of nano-clay is also added in step a); 0.01-0.05 part by weight of an acidic catalyst is also added in step b).

6. The preparation method of the epoxy resin-based composite insulating material with high electrical strength according to claim 5, characterized in that, The acidic catalyst is one of acetic acid or citric acid.

7. The preparation method of the epoxy resin-based composite insulating material with high electrical strength according to claim 5, characterized in that The ultrasonic power is 200 w.

8. The preparation method of the epoxy resin-based composite insulating material with high electrical strength according to claim 5, characterized in that, The drying temperature is 60-80 °C.

9. The preparation method of the epoxy resin-based composite insulating material with high electrical strength according to claim 5, characterized in that, The nano-clay has also been subjected to a composite treatment with graphene quantum dots, which specifically includes the following steps: 1) Add 5 parts by weight of nano-clay to a container containing 100 parts by volume of DMF, disperse it under ultrasonic environment for 30-60 min to make the nano-clay preliminarily dispersed evenly; then, slowly add 50 parts by volume of a graphene quantum dot solution with a concentration of 1 mg / mL, and continue to ultrasonically disperse for 2-4 h to make the graphene quantum dots fully contact and interact with the nano-clay; 2) Centrifuge and separate the ultrasonically dispersed mixed solution to remove impurities and unreacted substances in the supernatant, and then wash the precipitate with DMF multiple times to ensure that the surface impurities are completely removed; 3) Dry the washed precipitate in a vacuum oven to obtain nano-clay-graphene quantum dot composite powder, which can be used for composite modification of nano-silica with perfluoroalkylsilane.

10. The preparation method of the epoxy resin-based composite insulating material with high electrical strength according to claim 5, characterized in that, In step 2), the rotational speed is controlled at 5000 - 8000 rpm and the time is 15 - 30 min; in step 3), the temperature is set at 60 - 80 °C and the drying time is 12 - 24 h.

Citation Information

Patent Citations

  • Degradable organic amines and organic aromatic ammonium salts latent epoxy resin curing agent and application

    CN103254406A

  • High-thermal conductivity electrical insulation cement and preparation method thereof

    CN104629266A

  • Fluorine-containing epoxy resin for high-performance carbon fiber prepreg and preparation method thereof

    CN116675951A

  • Epoxy resin composite material as well as preparation method and application thereof

    CN117050475A

  • Fluorinated epoxy fluorocarbon coating compositions and the process to make the same

    CN86108642A

Cited By

  • Temperature-resistant high-voltage insulation epoxy resin composition and preparation method thereof

    CN121022038A

  • Fluorocarbon modified polymer insulating material and insulating joint

    CN122609015A